Ranking of Psychogenic Factors in Persons Temporarily Displaced from the Area of Counter-Terrorism Operation Suffering from Neurotic Disorders - HimchanА.; Suvorova-Grigorovich, G. (Psychiatry, Neurology and Medical Psychology, 2016)
We have observed 110 persons temporarily displaced from the area of counterterrorism operation suffering from neurotic disorders using clinical and psychometric methods. Among factors causing neurotic disorders leading role was taken by prolonged situational, second acute situational, last place was occupied catastrophic psychogenicfactors.The main part of patients have had a combination of factors, both acute and chronic.